IMPLEMENTATION OF GRAPH BASED PATH PLANNING ALGORITHMS FOR INDOOR NAVIGATION - SYED KHAIZURA, SYED HUSEIN KAMIL (2018)
Path planning algorithms is very important in autonomous mobile robots, this is to ensure that the robot can travel to its target location independently with efficient usage of time and energy. In this study, we are looking at the performance of four graph-based path planning algorithms which is Breadth First Search, Depth First Search, Dijkstra and A*, when implemented in real world applications. Also, to observe the advantages and disadvantages of these four path planning algorithms. In this case, we are splitting the project task into two parts, one of which is to implement the four algorithms on a small mobile robot, which will traverse within an indoor environment. The map of the environment is split into a grid which has equal sizes to represent these nodes. In which the obstacles, start node and target node will be known in advance of starting the path planning algorithms. Based on the results of MATLAB simulation, the A* algorithm is the best algorithm in finding the shortest path with the least time taken. Thus, the A* algorithm is implemented in a small mobile robot, this is to see its effectiveness in real world application. The application in real world application has been done and its success rate is about 70 percent.